Desain dan Prototipe Integrasi IoT dalam Pertanian Hidroponik Cerdas Berbasis Energi Terbarukan - Wardhana, Agus Salim; Ferdiansyah, Muhammad; K, Siti Kholifah (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This research aims to develop a prototype for an Internet of Things-based automation system powered by renewable energy, specifically solar panels, to enhance the efficiency and productivity of hydroponic farming. The study addresses critical challenges, including high energy costs and the intensive monitoring demands of conventional hydroponic systems. The experimental methodology involves designing hardware featuring Arduino Uno as the central control unit, environmental sensors (DHT22) for real-time monitoring, and automated actuators such as water pumps, fans, and LED lights. The system integration process encompasses linking the hardware to an IoT interface, followed by rigorous functional testing to evaluate system stability, energy efficiency, and operational performance under varying environmental conditions. The results demonstrate that the prototype successfully operates the entire hydroponic system using energy exclusively from solar panels, eliminating reliance on conventional electricity. The system achieves precise control over critical plant growth parameters such as temperature, humidity, and lighting, with high operational stability observed during trials. This research makes a notable contribution by innovatively integrating IoT, automation, and renewable energy, thereby enhancing energy efficiency while delivering a sustainable and environmentally friendly hydroponic farming solution. The findings have significant practical implications, particularly for implementation in remote areas with limited access to electricity. Furthermore, the study paves the way for future developments, including applications in other agricultural systems and the integration of artificial intelligence to enhance predictive analytics and automated control.